A controlled therapeutic trial of long-term maintenance treatment of ulcerative colitis with sulphasalazine (Salazopyrin). Issue 12 (December 1973) - Dissanayake, A. S.; Truelove, S. C.
Abstract : Sixty-four patients with proven ulcerative colitis who had been maintained on sulphasalazine as their sole form of treatment for a minimum period of one year were entered into a controlled trial of sulphasalazine versus dummy tablets for a period of six months. All the patients admitted were not only symptom-free but also showed no evidence of inflammation on sigmoidoscopy and rectal biopsy. A patient was judged to have relapsed when there was a recurrence of colitic symptoms accompanied by sigmoidoscopic and histological evidence of inflammation. The patients who received dummy tablets had more than four times the relapse rate of those receiving sulphasalazine. The results were similar in patients who had been on maintenance treatment with sulphasalazine for less than three years before entry into the trial and in those who had been on this treatment for more than three years. It is concluded that maintenance treatment of ulcerative colitis with sulphasalazine should be continued indefinitely unless contraindicated by side effects.